Impact of Gas Saturation and Gas Column Height at the Base of the Gas Hydrate Stability Zone on Fracturing and Seepage at Vestnesa Ridge, West-Svalbard Margin - Hariharan Ramachandran; Andreia Plaza-Faverola; Hugh Daigle (Energies, 2022)
The Vestnesa Ridge, located off the west Svalbard margin, is a >60 km long ridge consisting of fine-grained sediments that host a deep-marine gas hydrate and associated seepage system. Geological and geophysical observations indicate the predominance of vertical fluid expulsion through fractures with pockmarks expressed on the seafloor along the entire ridge. However, despite the apparent evidence for an extended free gas zone (FGZ) below the base of the gas hydrate stability zone (BGHSZ), present-day seafloor seepage has been confirmed only on the eastern half of the sedimentary ridge. In this study, we combine the relationships between aqueous phase pressure, capillary pressure, sediment clay fraction, porosity, and total stress to simulate how much gas is required to open preexisting fractures from the BGHSZ towards the seafloor. Data from four specific sites with different lithology and pressure regime along the ridge are used to constrain the simulations. Results demonstrate that fracturing is favored from the FGZ (with gas saturations < 0.1 and gas column heights < 15 m) towards the seafloor. Neglecting the capillary pressure overpredicts the size of the gas column by up to 10 times, leading to erroneous maximum gas vent volume predictions and associated ocean biosphere consequences. Further parametric analyses indicate that variations in the regional stress regime have the potential to modify the fracture criterion, thus driving the differences in venting across the ridge. Our results are in line with independent geophysical observations and petroleum system modeling in the study area, adding confidence to the proposed approach and highlighting the importance of the capillary pressure influence on gas pressure.